Does Extended Surgery Influence Health-Related Quality of Life in Patients With Rectal Cancer?. Issue 2 (February 2015) - Orsini, Ricardo G.; Vermeer, Thomas A.; Traa, Marjan J.; Nieuwenhuijzen, Grard A. P.; de Hingh, Ignace H. J. T.; Rutten, Harm J. T.
Abstract : BACKGROUND: In locally advanced rectal cancer, an extended resection peripheral to the mesorectal fascia is needed to achieve a radical resection. The influence of extended resections on health-related quality of life is unclear. OBJECTIVE: Differences in health-related quality of life and sexuality between patients receiving standard surgery and patients receiving extended surgery were examined, with a focus on age. DESIGN: Patients operated on for rectal cancer between 2000 and 2010 were selected from a database and invited to complete the European Organization for Research and Treatment of Cancer quality-of-life questionnaires (C30 and ColoRectal 38). SETTINGS: All patients were treated at the Catharina Hospital, Eindhoven, the Netherlands. PATIENTS: All patients received total mesorectal excision surgery or extended surgery for rectal cancer. MAIN OUTCOME MEASURES: Health-related quality of life and sexual activity was compared between patients treated with total mesorectal excision surgery and extended surgery and further stratified by age at the time of surgery (<70 and ≥70). RESULTS: Two hundred twenty-nine (64.1%) patients with standard surgery and 128 (35.9%) patients treated with extended resections responded. Extended surgery in patients <70 years resulted in lower body image compared with patients <70 years receiving standard surgery. Patients ≥70 years had lower sexual function and more male sexual dysfunction than patients <70 years undergoing standard surgery. In all groups, sexual activity dropped significantly after treatment. LIMITATIONS: No information was available of the patients' health-related quality of life before treatment except for the retrospective question about sexual activity. CONCLUSIONS: This study showed no major differences between patients undergoing total mesorectal excision surgery and those receiving extended surgery, with the exception of body image, which was significantly lower in patients <70 years undergoing extended surgery. In all patient groups, treatment for rectal cancer influenced sexual activity dramatically. Awareness of the impact of surgery on health-related quality of life and sexuality is needed.